The Made-Up State Technology, Trans Femininity, and Citizenship in Indonesia - Hegarty, Benjamin (Cornell University Press, 2022)
In The Made-Up State, Benjamin Hegarty contends that warias, who compose one of Indonesia's trans feminine populations, have cultivated a distinctive way of captivating the affective, material, and spatial experiences of belonging to a modern public sphere. Combining historical and ethnographic research, Hegarty traces the participation of warias in visual and bodily technologies, ranging from psychiatry and medical transsexuality to photography and feminine beauty. The concept of development deployed by the modern Indonesian state relies on naturalizing the binary of "male" and "female." As historical brokers between gender as a technological system of classifying human difference and state citizenship, warias shaped the contours of modern selfhood even while being positioned as nonconforming within it. The Made-Up State illuminates warias as part of the social and technological format of state rule, which has given rise to new possibilities for seeing and being seen as a citizen in postcolonial Indonesia.